2020
DOI: 10.1136/jitc-2019-000374
|View full text |Cite
|
Sign up to set email alerts
|

Tumor copy-number alterations predict response to immune-checkpoint-blockade in gastrointestinal cancer

Abstract: BackgroundDespite the great achievements made in immune-checkpoint-blockade (ICB) in cancer therapy, there are no effective predictive biomarkers in gastrointestinal (GI) cancer.MethodsThis study included 93 metastatic GI patients treated with ICBs. The first cohort comprising 73 GI cancer patients were randomly assigned into discovery (n=44) and validation (n=29) cohorts. Comprehensive genomic profiling was performed on all samples to determine tumor mutational burden (TMB) and copy-number alterations (CNAs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…In addition, Lu et al. 53 revealed that patients treated with immune checkpoint blockade therapy could receive a durable clinical benefit and achieve better survival if they exhibited a lower CNA burden. Gene mutation is another key component upon which we focused with respect to the three immunophenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lu et al. 53 revealed that patients treated with immune checkpoint blockade therapy could receive a durable clinical benefit and achieve better survival if they exhibited a lower CNA burden. Gene mutation is another key component upon which we focused with respect to the three immunophenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Several studies have indicated that CNVs identified in tumor tissue is related to the response to immunotherapy in patients with cancer. [31][32][33][34] A recent study found that HCC tumors with a low burden of broad copy number chromosomal alterations display higher immune infiltration and have a better response rate to anti-PD-1 inhibitors than those with a median/high broad copy number. 35 Moreover, Davoli et al 31 found that a higher CNV burden in tumor tissue correlated with immune escape and poorer survival in patients with metastatic melanoma treated with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Davoli et al (2017) performed a bioinformatic analysis on 5255 tumor and normal samples representing 12 cancer types and found that reduced expression of markers for cytotoxic immune cell infiltrates was correlated with high levels of SCNAs [300]. Recently, further bioinformatic studies in different types of cancers confirmed that elevated levels of SCNAs are correlated with a decreased immune signature or an increase in pathways referring to immune suppression [301][302][303]. As mentioned in the previous chapter, hypoxia is responsible for a moderate genome instability, due to the transcriptional and translational repression of genes involved in DNA damage repair pathways.…”
Section: Tumor Cell-intrinsic Signalingmentioning
confidence: 99%